The Black Ecstatic - Desirée de Jesús (Screenworks)
Critically lauded as one of 2020’s best films, Steve McQueen’s Lovers Rock is an intimate look at black joy during a fraught period of high unemployment and the state-sanctioned criminalization of racialized communities in early 1980s Britain. My video essay ‘The Black Ecstatic’ concentrates on a sequence in this musical and explores how attending to sound enables us to think across generations of Black diasporic dreaming, striving, believing, and resisting bodies.